Strategies for Site‐Specific Labeling of Receptor Proteins on the Surfaces of Living Cells by Using Genetically Encoded Peptide Tags. (26th February 2021) - Wolf, Philipp; Gavins, Georgina; Beck‐Sickinger, Annette G.; Seitz, Oliver
Abstract: Fluorescence microscopy imaging enables receptor proteins to be investigated within their biological context. A key challenge is to site‐specifically incorporate reporter moieties into proteins without interfering with biological functions or cellular networks. Small peptide tags offer the opportunity to combine inducible labeling with small tag sizes that avoid receptor perturbation. Herein, we review the current state of live‐cell labeling of peptide‐tagged cell‐surface proteins. Considering their importance as targets in medicinal chemistry, we focus on membrane receptors such as G protein‐coupled receptors (GPCRs) and receptor tyrosine kinases (RTKs). We discuss peptide tags that i) are subject to enzyme‐mediated modification reactions, ii) guide the complementation of reporter proteins, iii) form coiled‐coil complexes, and iv) interact with metal complexes. Given our own contributions in the field, we place emphasis on peptide‐templated labeling chemistry. Abstract : Fluorescence microscopy imaging provides information about the localization and trafficking of G protein‐coupled receptors and receptor tyrosine kinases. To visualize these proteins, reporter groups must be introduced on the surface of live cells. This review discusses live‐cell protein labelling by small, genetically encoded peptide tags serving as enzyme substrates or recognition sites for interactions with proteins, coiled‐coil peptides and metal reagents.